Behavioral and physiological responses induced by ozone in five Brazilian populations of Rhyzopertha dominica. (May 2017) - Velasquez, Luz Paola Grisales; Faroni, Lêda Rita D'Antonino; Pimentel, Marco Aurélio Guerra; Heleno, Fernanda Fernandes; Prates, Lucas Henrique Figueiredo
Abstract: This study evaluated locomotory and respiratory responses induced by ozone at a concentration of 500 ppm in five Brazilian populations of Rhyzopertha dominica (Coleoptera: Bostrichidae). Toxicity and body mass were also assessed to establish their relationship with behavioral patterns. The results indicated that none of the evaluated populations of Rhyzopertha dominica showed resistance to ozone. No significant correlations were observed between ozone toxicity and locomotory behavioral patterns. Moreover, no significant correlations were found between ozone toxicity and the respiratory rate of Rhyzopertha dominica . Ozone is a potential alternative for phosphine resistance management, and its rapid degradation constitutes an advantage for the environment.